Pengaruh Co-Creation terhadap Brand Awareness - Fauziyyah, Sifa; Muttaqin, Rizqi (SAFE-Network, 2024)
The purpose of this study was to determine the effect of Co-Creation between Dermies Hello Glow by ERHA and Teh Botol Sosro on Brand Awareness of Dermies Hello Glow by ERHA products. The respondents studied were Indonesian women who use skincare products. The purposive sampling method was used for research sampling. There were 107 respondents who fit the predetermined criteria. This research tests or analyzes data using SPSS 23 software. The results show that Co-Creation has a positive and significant impact on Brand Awareness.